(2/3)x - (1/5) y = 10

to solve for x in terms of y:

(2/3)x - (1/5) y = 10

(2/3)x = 10 + (1/5)y

x = (10 + (1/5)y)(3/2)

x = 15 + 3/10 y

**if y = 0; x = 15**

to solve for y in terms of x:

(2/3)x - (1/5) y = 10

-(1/5) y = 10 - (2/3)x

y = (10 - (2/3)x) -5

y = -50 + 10/3 x

**if x = 0; y = -50**

**slope = 10/3 **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now